Traditional authorities and co-management of protected areas in South Africa: the case of Dwesa-Cwebe Nature Reserve in the Eastern Cape - Tsawu, Simphiwe (African Studies, 2023)
This thesis examines the role of traditional authorities in the post-land claim co-management of protected areas in the former Bantustans of South Africa, using the Dwesa-Cwebe Nature Reserve (DCNR) in the Eastern Cape as a case study. The DCNR was one of the first successful land claims involving a protected area under South Africa's post-1994 land restitution policies, and one of the earliest communities to create new landowner institutions under tenure reform policies. Two theoretical debates – the critical and the supportive perspectives – provide the framework for this study and help in assessing how theorists viewed the role of traditional authorities in the context of protected area management in rural areas. I argue that traditional authorities should not be regarded as guests in their areas of control; instead, a nuanced understanding of their role in postland claim co-management of protected areas such as Dwesa-Cwebe is required as they, in turn, are held accountable by communities that they “govern”. Such contexts require mechanisms that recognise both traditional authorities and elected representatives as equal partners in the post-land claim co-management of protected areas. The accommodation of traditional authorities is unavoidable because many inhabitants of former Bantustans continue to respect them. Furthermore, the state increasingly empowers them. The people of Dwesa-Cwebe held their traditional authorities accountable for their former roles in land dispossession and in enforcing brutal state restrictions on access to the natural resources in the DCNR. This they did by excluding traditional leaders from the land claim process and the land tenure and management institutions – the Land Trust and Communal Property Associations. However, when problems arose with the Land Trust, traditional authorities stepped in and removed the Trust, effectively holding that body to account. During this process, the state came out clearly in support of traditional authorities. The thesis concludes that as long as traditional authorities are empowered by the state and enjoy popularity in rural communities such as Dwesa-Cwebe, their role in the co-management of protected areas will remain significant and necessary. In examining and assessing the role that traditional authorities play in rural areas, particularly with regard to communal land in protected areas, I employed a qualitative approach. I mainly used a combination of semi-structured interviews, informal conversational interviews and participant observation to compile and gauge the views of people in the area, as well as official government documentation, minutes of meetings and a range of secondary sources.